Marketing technologies promoting organic products in the minds of digitalization (Economics and region, 2022)
The organic food market is the most steadily growing market in recent decades, attracting the attention of more and more producers and consumers, and the COVID-19 pandemic has only strengthened the position of organic food products. According to these conditions, consumers began to pay more and more attention to their health and take care of the environment. The demand for organic food products has become one of the component changes affecting the modern consumption pattern. The factors limiting the development of the domestic organic product were investigated, among which the greatest influence is insufficient institutional support and the level of professional knowledge and experience in this field, as well as high trade surcharges on organic food products in the retail networks of Ukraine. The main sales channels for organic products remain points of sale, the Internet/social networks, specialized articles, fairs and events, and television advertising. To analyze broadly the traditional marketing technologies of promotion of organic products used by producers. The most popular remain: sales features, participation in inserts and fairs, Internet marketing, e-mail mailing, marketing in social networks, branding. By studying the experience of the most famous domestic organic brands, we identified new marketing technologies and tools that are used in the practice of these companies. Among the most effective marketing technologies and communication tools, in the conditions of digitalization, is the use of the storytelling approach, which positively affects the attitude of consumers to the brand. The use of SEO promotion increases the effectiveness of searches for competitive keywords and helps attract potential consumers to the site and make it more popular among them. Influence-marketing has become a full-fledged promotion tool, which in a few years has changed from an auxiliary marketing tool to an industry. Normcore marketing, which is gaining momentum in the world, especially in the field of production of organic products, remains less popular in the domestic territory. In the conditions of digitization, managers of organic production also need new marketing technologies and approaches that also interest and form consumer loyalty in order to achieve stable competitive positions in the market.
Keywords: marketing technologies; marketing; market; marketing tools; digitalization; organic producers